Using the accelerated Brazilian concrete prism test (ABCPT) to evaluate alkali aggregate reaction (AAR) - Sanchez,L. (2011)
There are many test methods used in the laboratory to detect potential alkali-aggregate reactions (AAR). However, up to now, there is no consensus if they are reliable and efficient. This work presents the development of a new and accelerated concrete prism test called ABCPT (accelerate Brazilian concrete prism test) as an attempt to create a reliable and fast test that can analyze and classify the potential reactivity of aggregates in the laboratory. For this research, six aggregates from different lithotypes were used. The methods CPT, ACPT and ABCPT were carried out with all the aggregates and a comparative analysis among all tests was performed. ABCPT seems to have a great potential to analyze and classify aggregates in the laboratory, although it needs further testing with other lithotypes to be confirmed as feasible.